The hematological and histological studies for the hepatoprotective-like effect of the hydromethanolic extract and the fractions of Viola serpens Wall. - Ghaffar, Rukhsana; Ahmad, Manzoor; Khan, Haroon; Nazir, Nausheen; Sultana, Nuzat; Alsharif, Khalaf F; Khan, Jehangir; Naz, Attiqa (Cellular and Molecular Biology, 2022)
Traditionally, Viola serpens has been used in the treatment of several human disorders including liver diseases without any scientific evidence. As the current therapies are not very effective and face challenges of unwanted effects and patient compliance, therefore more effective and safe agents are highly needed. The current study aimed to evaluate the hepatoprotective potential of the crude extract and subsequent fractions of the whole plant in the in-vivo model using various hematological and histopathological parameters followed by an HPLC study for the identification of phenolic compounds. Rabbits (1000-1200 g) were used in the study. Paracetamol (2g) was used to induce hepatotoxicity in experimental rabbits. The plant extract was used in two doses (150 and 300 mg/kg body weights) for eight days. The hematological parameters AST, ALT and ALP values were determined along with the histopathology of the liver. Phenolic compounds were identified by high-performance liquid chromatography (HPLC) Agilent-1260 infinity from their retention time, UV spectra and available standards while quantification was done taking the percent peak area. The doses 150 and 300 mg/kg body weight seemed to be more effective. The hematological values and the histopathological slides show the hepatoprotective effect of the plant. Regeneration indicated the presence of nuclei, nuclear cleaning, prominent nucleoli, RBC’s, central veins and plates of hepatocytes. The HPLC studies revealed the presence of a number of phenicol compounds. The crude extract and the subsequent fractions of the plant possess strong hepatoprotective activity, providing a scientific rationale for its uses in the treatment of liver toxicities.